Arahan Pola Pengembangan Kawasan Perkotaan Sinjai - Risnawati K; Andi Muhammad Ikhsan (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2022)
This research is about the direction of the development pattern of the Sinjai Urban Area. The main problem is how to control development in the Sinjai Urban Area. This problem is seen by the conditions of development that occur in the Sinjai Urban Area. Thus, this study uses descriptive analysis by looking at the land use system that is currently developing and identifying the area development system in terms of development control, namely data analysis that aims to describe the state of the observation area or according to the data obtained in the form of decomposition and analysis is carried out. to consider the existing physical conditions at the research location in order to minimize development in the Sinjai Urban Area